2008
DOI: 10.1038/nature06489
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cells initiating human melanomas

Abstract: Tumour-initiating cells capable of self-renewal and differentiation, which are responsible for tumour growth, have been identified in human haematological malignancies 1,2 and solid cancers [3][4][5][6] . If such minority populations are associated with tumour progression in human patients, specific targeting of tumour-initiating cells could be a strategy to eradicate cancers currently resistant to systemic therapy. Here we identify a subpopulation enriched for human malignantmelanoma-initiating cells (MMIC) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
1,300
5
19

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,304 publications
(1,378 citation statements)
references
References 29 publications
33
1,300
5
19
Order By: Relevance
“…[5][6][7][8][9] As shown in Figure 1b, all cell lines generated tumorospheres, and flow cytometry analyses showed that CD44 þ CD24 À population was highly enriched in tumorospheres (Supplementary Figure S1A). We sorted CD44 þ CD24 À cells from spheres of prostate and breast cancer using fluorescence-activated cell sorting (FACS) and achieved a purity of 495% as judged by postsorting flow analysis (Figure 1c).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…[5][6][7][8][9] As shown in Figure 1b, all cell lines generated tumorospheres, and flow cytometry analyses showed that CD44 þ CD24 À population was highly enriched in tumorospheres (Supplementary Figure S1A). We sorted CD44 þ CD24 À cells from spheres of prostate and breast cancer using fluorescence-activated cell sorting (FACS) and achieved a purity of 495% as judged by postsorting flow analysis (Figure 1c).…”
Section: Resultsmentioning
confidence: 91%
“…Collectively, our data suggest that both CSCs and spheres exhibited diverse stem cell-associated characteristics, consistent with previous reports. [5][6][7][8][9] CSCs overexpressed BAD with elevated phosphorylation. As CSCs are resistant to drugs 11 and phosphorylated BAD correlates with drug resistance in cancer patients, 25 we determined the level of BAD expression and phosphorylation in CSCs and tumorospheres.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, stem cell research has opened up new and intriguing horizons that may enable better understanding of development of cancer in general and melanoma in particular. [6][7][8][9] Stem cells are slowly proliferating self-renewing cells that are able to differentiate into cell types of multiple lineages (ie, multipotent stem cells) or of one lineage (ie, unipotent stem cells). Researchers have identified stem cells of melanocytic lineage in the human hair follicle, the epidermis, and recently also in the dermis.…”
mentioning
confidence: 99%
“…When acute myeloid leukemia patients are re-examined after chemotherapy, the persistence of CD34 þ CD38 À cells (proposed to be LICs) predicts a high risk of relapse (van Rhenen et al, 2005). Similarly, the presence of stemness markers within the tumor cells of melanoma and breast cancer patients (ABCB5 þ and CD44 þ , respectively) correlates with a higher rate of cancer progression and poor prognosis (Shipitsin et al, 2007;Schatton et al, 2008). As highlighted above, the eradication of LICs in APL upon treatment with retinoic acid and arsenic supports the concept that agents targeting TICs will lead to complete cure.…”
Section: Novel Paradigms For Cancer Therapy V Pavet Et Almentioning
confidence: 99%